Enhancing Worker Health Through Clinical Decision Support (CDS): An Introduction to a Compilation. Issue 11 (November 2017) - Filios, Margaret S.; Storey, Eileen; Baron, Sherry; Luensman, Genevieve B.; Shiffman, Richard N.
Abstract : Objective: This article outlines an approach to developing clinical decision support (CDS) for conditions related to work and health. When incorporated in electronic health records, such CDS will assist primary care providers (PCPs) care for working patients. Methods: Three groups of Subject Matter Experts (SMEs) identified relevant clinical practice guidelines, best practices, and reviewed published literature concerning work-related asthma, return-to-work, and management of diabetes at work. Results: SMEs developed one recommendation per topic that could be supported by electronic CDS. Reviews with PCPs, staff, and health information system implementers in five primary care settings confirmed that the approach was important and operationally sound. Conclusion: This compendium is intended to stimulate a dialogue between occupational health specialists and PCPs that will enhance the use of work information about patients in the primary care setting.